Inherited functional variants of the lymphocyte receptor CD5 influence melanoma survival. Issue 6 (31st May 2016) - Potrony, Miriam; Carreras, Esther; Aranda, Fernando; Zimmer, Lisa; Puig‐Butille, Joan‐Anton; Tell‐Martí, Gemma; Armiger, Noelia; Sucker, Antje; Giménez‐Xavier, Pol; Martínez‐Florensa, Mario; Carrera, Cristina; Malvehy, Josep; et al.
Abstract : Despite the recent progress in treatment options, malignant melanoma remains a deadly disease. Besides therapy, inherited factors might modulate clinical outcome, explaining in part widely varying survival rates. T‐cell effector function regulators on antitumor immune responses could also influence survival. CD5, a T‐cell receptor inhibitory molecule, contributes to the modulation of antimelanoma immune responses as deduced from genetically modified mouse models. The CD5 SNPs rs2241002 (NM_014207.3:c.671C > T, p.Pro224Leu) and rs2229177 (NM_014207.3:c.1412C > T, p.Ala471Val) constitute an ancestral haplotype (Pro224‐Ala471) that confers T‐cell hyper‐responsiveness and worsens clinical autoimmune outcome. The assessment of these SNPs on survival impact from two melanoma patient cohorts (Barcelona, N  = 493 and Essen, N  = 215) reveals that p.Ala471 correlates with a better outcome (OR= 0.57, 95% CI = 0.33–0.99, Adj. p  = 0.043, in Barcelona OR = 0.63, 95% CI = 0.40–1.01, Adj. p  = 0.051, in Essen). While, p.Leu224 was associated with increased melanoma‐associated mortality in both cohorts (OR = 1.87, 95% CI = 1.07–3.24, Adj. p  = 0.030 in Barcelona and OR = 1.84, 95% CI = 1.04–3.26, Adj. p  = 0.037, in Essen). Furthermore survival analyses showed that the Pro224‐Ala471 haplotype in homozygosis improved melanoma survival in the entire set of patients (HR = 0.27, 95% CI 0.11–0.67, Adj. p  = 0.005). These findings highlight the relevance of genetic variability in immune‐related genes for clinical outcome in melanoma. Abstract : What's new? Accumulating clinical and experimental evidence indicates that the T‐cell modulatory properties of CD5 might play a role in the antitumor immune response by acting as a putative immune regulator checkpoint. Here, the authors examined the association between CD5 allelic variations at SNPs rs2229177 and rs2241002 and clinical outcome of malignant melanoma in two independent cohorts. They found that CD5 functional variants influence melanoma outcome, illustrating the contribution of the genetic variability of the host's immune response on patient survival prospects. This study supports the CD5 immune checkpoint as a new target for the improvement and development of new cancer immunotherapies.